SEEPAGE AND SLOPE STABILITY ANALYSIS OF LEVEES SUBJECTED TO FLOODING (THEORITICAL STUDY) - Zaki Mohsin Al-Qasi, Atheer; Majid Abbas Al-Rammahi, Ayaat (Journal of Engineering and Sustainable Development, 2018)
In this study, a levee is modeled by using ANSYS 11.0 to be analyzed for seepage and slope stability. One of the main causes of levees failure is the destabilizing effect of seepage forces of the infiltrating water during floods. The existence of the analogy between seepage and heat diffusion made it possible to analyze the hydraulic problem with ANSYS/THERMAL. In addition, the slope stability is analyzed for different cases by Strength Reduction Finite Element Method. The results showed that strength reduction technology was suitable for simple homogeneous side slope stability analysis. To verify the accuracy of the analysis, the results are compared with a case that studied by finite element program SEEP/W and SLOPE/W (GEOSLOPE 2007) has been taken and modeled by ANSYS/APDL. The results showed close to them for seepage and slope stability analysis. In other hand, some parameters such as flood conditions, permeability, slopes, and soil parameters (cohesion and angle of internal friction) are taken to study there effects on the seepage and slope stability. It is found that, the steep slope for cohesion less soil in high flood level is the most critical section of levees for both static and seismic load. Moreover, hydraulic behavior of clay core in a levee section subjected to flooding is investigated with help of numerical modeling.